APPLYING UTAUT2 TO AI-DRIVEN IELTS PREPARATION: A STUDY OF CHATGPT ADOPTION - Fitria, Vany; Hakim, Luqman; Mardiani, Desika Putri; Febryanti, Dita Indra; Majid, Gilang Maulana (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
This study explores the application of UTAUT2 in adopting ChatGPT for IELTS preparation, identifying key influencing factors. A scenario-based online survey with 168 Indonesian social media users was analyzed using partial least square-structural equation modeling (PLS-SEM). Findings reveal that performance expectancy, effort expectancy, social influence, and habit significantly drive behavioral intention. Users perceive ChatGPT as an effective tool for improving IELTS scores through personalized learning and appreciate its ease of use. Social influence from educators and peers also plays a crucial role, while habitual use reinforces trust in ChatGPT’s reliability. Interestingly, facilitating conditions, hedonic motivation and price value were non-significant. Specifically, cost concerns may be less relevant given ChatGPT’s free-tier accessibility, and hedonic motivation may be secondary in a goal-oriented setting like IELTS preparation. These non-significant results might also be shaped by Indonesia’s collectivist culture, where social influence outweighs individualistic motivations such as enjoyment. These findings suggest that the UTAUT2 model may require contextual adaptation for educational technologies, particularly in settings where functionality and effectiveness outweigh cost considerations. This study highlights the need to prioritize performance, ease of use and social influence to drive AI adoption in education.